(untitled) (Asian Journal of Social Science Studies, 2016)
Employment is one of the important social determinants of mental health and hence social integration. This concept is however not duly recognized and so is its application. It is reasonable to infer this as a partial attribute of the unemployment issues in the rehabilitants with schizophrenia. Public health professionals should collaborate with rehabilitation professionals to advocate in the open job markets the crucial roles of employment as a social determinant in facilitating social integration of people with schizophrenia. Further efforts have to be made to analyze the problems of unemployment in the population of those with schizophrenia with reference to its social determinant nature and other associated issues, and then incorporate it into the agenda for public mental health system.